Dancing home - Ada, Alma Flor; Zubizarreta, Gabriel M. (New York Atheneum Books for Young Readers, 2013)
When Margie's cousin Lupe comes from Mexico to live in California with Margie's family, Lupe must adapt to America, while Margie, who thought it would be fun to have her cousin there, finds that she is embarrassed by her in school and jealous of her at home.
Based on the poem A Margarita by Ruben Dario.
960L
101906
Keywords: Mexican Americans -- California; Families; Cousins; Fathers and daughters; Fiction; Juvenile works